Growth hormone, insulin-like growth factor-I and its binding proteins in the follow-up of acromegaly. - Wass, J (1997)
Elevated growth hormone is a cardinal feature of acromegaly from the biological view point. Growth hormone stimulates IGF-I secretion and that of its major binding protein IGFBP-3. In these circumstances, where hyperinsulinaemia is present, IGFBP-1 levels, which are inversely related to insulin, are suppressed. Failure of suppression of growth hormone after oral glucose (> 2 mU/l (1 microgram/l) is the cardinal biochemical feature of acromegaly. IGF-I values at diagnosis are almost invariably raised. There is some overlap in the value of basal IGFBP-3 between normal subjects and acromegalics. For monitoring purposes, growth hormone values, either basal or during the day are useful. There is overlap in the values of IGF-I and IGFBP-3 between normal subjects and patients on treatment. Prognosis in acromegaly is determined by persistent elevation of growth hormone levels above 5 mU/l (2.5 micrograms/ l). More data are required for the prognostic use of IGF-I.